An investigation into the errors in pronouncing english long and short vowels of english- majored juniors in university of da nang- university of foreign language studies - Trần;Thị Thu Hiền; Phan Văn Hòa (ĐHĐN : ĐHĐN., 2015)
Nowadays, it is inevitably that English has become one of the most popular foreign languages that the students desire to master. There have been a number of the students feels ashamed at their inappropriate pronunciation also wonder why they are always considered as Vietnamese – English speakers at any time. Others encounter they cannot speak or listen to English because of their incorrect pronunciation. From the reasons above, it can be seen that inappropriate pronunciation has not only posed numerous problems for the students in English using process but also prevented them from improving communication skills. The thesis is conducted to bring out the differences and similarities between English and Vietnamese vowel system. Other aim of the study is to enable the English-majored juniors to obtain certain clearance between long and short vowels, which somewhat contributes to assist them for a better communicating practice. Besides, the aim of the study is to bring out the reasons causing the English- majored juniors errors. The study is aimed at demonstrating the main problems and suggesting some techniques related to vowel sounds including /i: / - /I/, /ɔ: / - /ɒ/, /u: / - /ʊ/, /æ/ - /e/. Questionnaires and recording were employed as the main methodologies for the research. I involved English – majored juniors in Department of English only, specifically they were students from 11CNA07 and 11CNA08 including 85 students. The study found that almost University of Foreign Language Studies’ English – majored juniors come to be aware of the difference between long and short vowels. As displayed in the results of questionnaire, nearly half 11CNA07 and 11CNA08 juniors asserted that they are able to distinguish between long and short vowels. It is also quite true for the results from recording.
Keywords: errors in pronouncing english long and short vowels of english- majored juniors in university of da nang- university of foreign language studies; errors in pronouncing english long -- short vowels of english- majored juniors